2017
DOI: 10.26817/16925777.364
|View full text |Cite
|
Sign up to set email alerts
|

Exploring English Language Teaching in an Ecuadorian Urban Secondary Institution

Abstract: This article presents a case study focused on the pedagogy of nine English language teachers' pedagogy in Ecuador. The significance of this study is its potential to inform practitioners, teacher educators, and policymakers in countries where teachers need to be prepared to teach in multilingual settings, such as Ecuador. Data analyses of nine observations of practicing teachers seems to suggest the curriculum used to prepare English teachers does not fully meet the educational needs of teachers or students. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The shift in pedagogical approach requires teachers to undergo professional development training as part of their preparation; however, isufficient training and courses were presented in Ecuador (Burgin & Daniel, 2017) before and during the early stages of curriculum implementation. Without adequate training, teachers often struggle with the demands of the curriculum, which influence their performance of the pedagogical approaches prescribed by the curriculum.…”
Section: Pedagogical Approachesmentioning
confidence: 99%
“…The shift in pedagogical approach requires teachers to undergo professional development training as part of their preparation; however, isufficient training and courses were presented in Ecuador (Burgin & Daniel, 2017) before and during the early stages of curriculum implementation. Without adequate training, teachers often struggle with the demands of the curriculum, which influence their performance of the pedagogical approaches prescribed by the curriculum.…”
Section: Pedagogical Approachesmentioning
confidence: 99%
“…The study of Burgin and Daniel (2017) affirms that teachers need to undergo professional development training to acquire the pedagogical content knowledge of a particular subject so that they can face the challenges posed by curriculum change. In enhancing and improving learner performance, teacher experience appears to have played a pivotal role, that is, higher teacher experience led to an improvement in student performance (Dada 2016).…”
Section: Teaching Life Sciences With or Without Relevant Qualificationsmentioning
confidence: 99%
“…A plethora of educational reforms introduced by departments of education forces teachers to employ teaching methods that are different from the ones they are used to (Berland et al 2016;Marco-Bujosa et al 2017). The effective implementation of new policies requires teachers' professional development to increase their pedagogical content knowledge (Bunch 2012;Burgin and Daniel 2017;Vold 2017). According to Burgin and Daniel (2017), normally, teachers are not well trained to deliver the life sciences content effectively.…”
Section: Factors That Influence the Effective Teaching Of Life Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry has acknowledged the crucial role of constant professional training of EFL teachers in the in-service (MinEduc, n.d.) sector to help teachers cope with the pedagogical and content challenges in implementing the curriculum in their classrooms. Several studies have revealed the lack of professional development programs for EFL in-service teachers in Ecuador (Burgin & Daniel, 2017;Villafuerte-Holguin & Macías-Mosquera, 2020); however, the few training programs implemented lack research to determine their effectiveness. According to Calle et al (2012Calle et al ( , 2015, it is necessary to expand research studies on the impact of professional development and teacher training while taking diverse educational contexts in Ecuadorian classrooms into account.…”
Section: Status Of Professional Development In Efl In Ecuadormentioning
confidence: 99%